HIV-related arterial stiffness in Malawian adults is associated with proportion of PD-1 expressing CD8 T-cells and reverses with anti-retroviral therapy - Kelly, C; Mwandumba, HC; Heyderman, RS; Jambo, K; Kamng'ona, R; Chammudzi, M; Sheha, I; Peterseon, I; Rapala, A; Mallewa, J; Walker, AS; Klein, N; et al. (Oxford University Press, 2019)
Background The contribution of immune activation to arterial stiffness and its reversibility in HIV-infected adults in sub-Saharan Africa is unknown. Methods HIV-uninfected and HIV-infected Malawian adults initiating antiretroviral therapy (ART) with CD4 <100 cells/l were enrolled (2-weeks post-ART for HIV-infected) and followed for 44-weeks. We evaluated the relationship between carotid femoral pulse wave velocity (cfPWV) and T-cell activation (HLADR+CD38+), exhaustion (PD1+) and senescence (CD57+), and monocyte subsets using normal regression. Results In 279 HIV-infected and 110 HIV-uninfected adults, 142(37%) had hypertension. HIV was independently associated with 12% higher cfPWV (p=0.02) at baseline, and week-10 (14% higher, p=0.02) but resolved by week-22. CD4 and CD8 T-cell exhaustion(PD1+) were independently associated with higher cfPWV at baseline (p=0.02). At 44-weeks, arterial stiffness improved more in those with greater decreases in %CD8 and %CD8PD1+ T-cells (p=0.01, p=0.03 respectively). When considering HIV-infected participants alone, adjusted arterial stiffness at week-44 tended to be lower in those with higher baseline %CD8PD1+ T-cells (p=0.054). Conclusions PD-1+ expressing CD8 T-cells are associated with HIV-related arterial stiffness, which remains elevated during the first three months on ART. Resources to prevent cardiovascular disease in sub-Saharan Africa should focus on blood pressure reduction, and those with low CD4 during early ART.